Carrier dynamics of a visible-light-responsive Ta3N5 photoanode for water oxidation. Issue 4 (11th December 2014) - Ziani, Ahmed; Nurlaela, Ela; Dhawale, Dattatray S.; Silva, Diego Alves; Alarousu, Erkki; Mohammed, Omar F.; Takanabe, Kazuhiro
Abstract : The physicochemical properties of a tantalum nitride (Ta3 N5 ) photoanode were investigated in detail to understand the fundamental aspects associated with the photoelectrochemical (PEC) water oxidation. Abstract : The physicochemical properties of a tantalum nitride (Ta3 N5 ) photoanode were investigated in detail to understand the fundamental aspects associated with the photoelectrochemical (PEC) water oxidation. The Ta3 N5 thin films were synthesized using DC magnetron sputtering followed by annealing in air and nitridation under ammonia (NH3 ). A polycrystalline structure with a dense morphology of the monoclinic Ta3 N5 films was obtained. A relatively low absorption coefficient (10 4 to 10 5 cm −1 ) in the visible light range was measured for Ta3 N5, consistent with the nature of the indirect band-gap. Ultra-fast spectroscopic measurements revealed that the Ta3 N5 with different thicknesses films possess low transport properties and fast carrier recombination (<10 ps). These critical kinetic properties of Ta3 N5 as a photoanode may necessitate high overpotentials to achieve appreciable photocurrents for water oxidation (onset ∼0.6 V vs. RHE).